Parallel inhibition of active force and relaxed fiber stiffness in skeletal muscle by caldesmon: implications for the pathway to force generation. - Brenner, B (1991)
In recent hypotheses on muscle contraction, myosin cross-bridges cycle between two types of actin-bound configuration. These two configurations differ greatly in the stability of their actin-myosin complexes ("weak-binding" vs. "strong-binding"), and force generation or movement is the result of structural changes associated with the transition from the weak-binding (preforce generating) configuration to strong-binding (force producing) configuration [cf. Eisenberg, E. & Hill, T. L. (1985) Science 227, 999-1006]. Specifically, in this concept, the main force-generating states are only accessible after initial cross-bridge attachment in a weak-binding configuration. It has been shown that strong and weak cross-bridge attachment can occur in muscle fibers [Brenner, B., Schoenberg, M., Chalovich, J. M., Greene, L. E. & Eisenberg, E. (1982) Proc. Natl. Acad. Sci. USA 79, 7288-7291]. However, there has been no evidence that attachment in the weak-binding states represents an essential step leading to force generation. It is shown here that caldesmon can be used to selectively inhibit attachment of weak-binding cross-bridges in skeletal muscle. Such inhibition causes a parallel decrease in active force, while the kinetics of cross-bridge turnover are unchanged by this procedure. This suggests that (i) cross-bridge attachment in the weak-binding states is specific and (ii) force production can only occur after cross-bridges have first attached to actin in a weakly bound, nonforce-generating configuration.